Direct oral anticoagulants for the treatment of acute venous thromboembolism in patients with cancer: a meta-analysis of randomised controlled trials. Issue 3 (28th September 2017) - Di Minno, Matteo Nicola Dario; Ageno, Walter; Lupoli, Roberta; Conte, Giulia; van Es, Nick; Buller, Harry R.; Dentali, Francesco
Venous thromboembolism (VTE) is a common complication in cancer patients [1, 2], associated with an 8–10% annual bleeding risk during anticoagulant therapy and a 10–20% annual risk of VTE recurrence [1, 3]. DOACs have a marginally higher antithrombotic efficacy and a comparable safety than VKA in cancer patients with VTE http://ow.ly/5lJN30dVVGF